PENGARUH KOMPETENSI, KOMPENSASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN (Studi Pada PT. Aquafarm Nusantara Semarang) - Rahayuningsih, Sri (Proceeding SENDI_U, 2017)
This study analyzed the effect of competence, compensationand development of Karier on the employee performance. development of Karier awarding on employees performance. Object of study in this paper is the PT Aquarfarm Nusantara Semarang. The sampling technique in this research is to use simple random sampling (random) sample of 95 respondents.The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the research are : (1) competence has a positive and significant impact influence on imployee permormance. (2) compensation has a positive and significant impact influence on employee performance and (3)development of Karier has a positive and significant impact influence on employee performance. Keywords : work discipline, Competence, Compensation Awarding, and Performance of Employees